2021
DOI: 10.3390/catal11091077
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate Enrichment of Niobium-Based Catalytic Surfaces in Relation to Reactions of Carbohydrate Biomass Conversion: The Case Studies of Inulin Hydrolysis and Fructose Dehydration

Abstract: In this work, some physical mixtures of Nb2O5·nH2O and NbOPO4 were prepared to study the role of phosphate groups in the total acidity of samples and in two reactions involving carbohydrate biomass: hydrolysis of polyfructane and dehydration of fructose/glucose to 5-hydroxymethylfurfural (HMF). The acid and catalytic properties of the mixtures were dominated by the phosphate group enrichment. Lewis and Brønsted acid sites were detected by FT-IR experiments with pyridine adsorption/desorption under dry and wet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 70 publications
(82 reference statements)
1
3
0
Order By: Relevance
“…These results emphasized the important role of Brønsted acid compared to Lewis acid in promoting inulin hydrolysis and fructose dehydration. Also, similar conclusions were found in other cases [20] . Meanwhile, the decisive contribution from Brønsted acid was further confirmed by the work of Chen et al [39] .…”
Section: Acid‐site Regulation In One‐pot Inulin Transformationsupporting
confidence: 83%
See 3 more Smart Citations
“…These results emphasized the important role of Brønsted acid compared to Lewis acid in promoting inulin hydrolysis and fructose dehydration. Also, similar conclusions were found in other cases [20] . Meanwhile, the decisive contribution from Brønsted acid was further confirmed by the work of Chen et al [39] .…”
Section: Acid‐site Regulation In One‐pot Inulin Transformationsupporting
confidence: 83%
“…Also, similar conclusions were found in other cases. [20] Meanwhile, the decisive contribution from Brønsted acid was further confirmed by the work of Chen et al [39] in which the sulfonic acid-functionalized Metal-Organic Frameworks (MOF) was employed for the dehydration of fructose to HMF, and the corresponding synthetic pathways and theoretical structures could be found in Figure 6b and 6c. It was found that the contribution of Brønsted acidity towards fructose dehydration was strongly correlated with the À SO 3 H grafting rate of the MOF-SO 3 H. Both fructose conversion and HMF selectivity were found to correlate positively and linearly with the density of sulfonic acid sites (acid density and S content) in MOF-SO 3 H, as shown in Figure 6d and 6e.…”
Section: Acid-site Regulation In One-pot Inulin Transformationmentioning
confidence: 80%
See 2 more Smart Citations